Decreasing Levels of BOD, COD and Oil in Palm Oil Mill Effluent (Pome) Using Scale Up Experiment of Symbiosis Mutualism Technology Between Microalgae Chorella Sp and Agrobost - Yelmira Zalfiatri; Fajar Restuhadi; Angga Pramana; Fajar Yuliandri (Politeknik Pertanian Negeri Payakumbuh, 2020)
Biological processing liquid sago waste is carried out by utilizing microlagae which are symbiotic with decomposer bacteria. The aim of this research was to get chosen treatment of microalgae Chlorella sp. as a reducing BOD, COD and Oil content in Palm Oil Mill Effluent with symbiotic mutualism between microalgae Chorella sp and Agrobost. This research used a Complete Randomized Design (CRD) with treatment 5 times and replication 3 times. This research was microalgae 800 ml/L (with abundance 6.883.000 cell/ml) in 6000 ml of total treatment solution with 5 treatments of Agrobost (0% v/v, 4% v/v, 8% v/v, 12% v/v, and 16% v/v). Data processing using ANOVA and DNRT 5%, the results showed that the concentration of Agrobost had significant affects for BOD, COD, oil and pH. The chosen treatment from the result of this research was 16% v/v which had the value BOD 89.10 mg/L, COD 297.67 mg/L, oil 2.85 mg/L, and pH 9.05.